Pemberdayaan Masyarakat Desa Kandri Melalui Pembuatan Pupuk Kulit Durian sebagai Paket Wisata Edukasi di Omah Pinter Petani - Intan Fatihatul Wahidah; Damai Sinar Pertiwi; Ervando Tommy Al Hanif (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
Community empowerment through community-based tourism is applied in the tourism village concept. Omah Pinter Petani is one of the tourist destinations developed through the concept of a Tourism Village in the City of Semarang. OPP has an agricultural educational tourism concept. The aim of this research is to examine the sustainability of Community Empowerment in making educational tour packages on durian skin fertilizer. By applying three methods, namely community empowerment, local potential base, and comprehensive activities. This has been carried out in the form of socialization, training and program realization, and monitoring and evaluation. With the results of processing durian skin waste combined with agricultural outbound activities as a tourism package at Omah Pinter Petani with the name 'Mas Duren'.